Tinjauan Yuridis dan Ekonomis terhadap Perbedaan Jenis-Jenis Koperasi dalam UU No. 25 Tahun 1992 dan Implementasinya - Batu Bara, Radja Marihat; Octaviani, Windi; Manurung, Cristina M; Putri, Dwi Nabilla; Matondang, Khairani Alawiyah (Universitas Pahlawan Tuanku Tambusai, 2025)
Cooperative Economics is a form of economic activity based on the principles of kinship and mutual cooperation, as stated in Article 33 of the Constitution of the Republic of Indonesia of 1945. In its implementation, cooperatives play a crucial role in improving the welfare of their members and the surrounding community through the collective management of enterprises based on justice and democratic principles. This study examines the concept of cooperative economics within the framework of the Indonesian National Qualification Framework (KKNI), particularly in the context of teaching the Cooperative Economics course. The discussion includes an understanding of fundamental principles, core values, objectives, and the role of cooperatives in supporting national economic development. The findings indicate that cooperatives function not only as economic entities but also as educational institutions and community empowerment agents that hold a strategic role in fostering people’s economic independence. Furthermore, this study emphasizes the importance of consistently applying cooperative principles to ensure that cooperatives can survive and compete amid the challenges of globalization.